2018
DOI: 10.1108/ijebr-11-2016-0367
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and effectuation for a successful business takeover

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 59 publications
(152 reference statements)
2
31
0
Order By: Relevance
“…Such youths would have many ways to overcome difficulties, and thus adapt to stressful life events, unlike necessity entrepreneurs. Besides, some empirical studies have shown that opportunity entrepreneurs are those who, beforehand, are endowed with entrepreneurial ingredients that drive their choice of an entrepreneurial career [18,73,96]. We do acknowledge that PsyCap dimensions are valuable and non-substitutable long term strategic resources [25], open to development and improvement [7,39].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Such youths would have many ways to overcome difficulties, and thus adapt to stressful life events, unlike necessity entrepreneurs. Besides, some empirical studies have shown that opportunity entrepreneurs are those who, beforehand, are endowed with entrepreneurial ingredients that drive their choice of an entrepreneurial career [18,73,96]. We do acknowledge that PsyCap dimensions are valuable and non-substitutable long term strategic resources [25], open to development and improvement [7,39].…”
Section: Discussionmentioning
confidence: 93%
“…Unlike necessity entrepreneurs, opportunity-driven entrepreneurs neither enter into entrepreneurship to survive unemployment or poverty nor because they are frustrated in their jobs or living conditions [17][18][19]28,31,35]. Opportunity entrepreneurs are those who have deliberately chosen entrepreneurship as a career option out of a passion for exploiting a perceived viable business opportunity [73]. They are motivated by the need for achievement or excellence instead of earning money, which is incidental and part of the measures of success [18,20].…”
Section: Effect Of Entrepreneurial Motivation On Business Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Through interview, one of the partner parties tries to convince the relevant participant of the dialogue about different forms and ways of behavior in terms of having united interest in products/services with the possibility of exploring or exchanging business offers, claims [11]. Authors [2], [7], [8] and [40] see business negotiation as an interactive communication process which might occur whenever we want something from someone else or when someone wants something from us.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Slow pace during business negotiation is logically beneficial as it blunts emotions and supports rational, conceptual thinking which avoids rapid reflection and, in most cases, suppresses random, unreasonable, and often squeamish decisions, says [33]. In order to gain customer´s/client´s confidence, business negotiator uses abilities to persuade, negotiate and realize real ideas and to manage situations and people, as communication is a decision-making power, expresses [7] and [30]. "Those who learn how to effectively use it might change own view on the world and even the view through which the world looks at them" [6].…”
Section: Literature Reviewmentioning
confidence: 99%